Essentials of Terror Medicine - Shapira, Shmuel; Hammond, Jeffrey; Cole, Leonard (Springer New York : Imprint: Springer, 2009)
A new field of medicine has emerged as a result of the global proliferation of terrorism. Terror medicine is related to emergency and disaster medicine but focuses on the constellation of medical issues uniquely related to terrorist attacks. The field encompasses four broad areas: Preparedness Incident management Mechanisms of injuries and responses Psychological consequences. In Essentials of Terror Medicine, these core concerns are addressed by a distinguished international authorship that has been brought together by the three editors of this volume, who themselves are recognized experts in relevant disciplines: Shmuel Shapira, epidemiology and hospital administration; Jeffrey Hammond, trauma surgery and emergency response; Leonard Cole, bioterrorism and public policy. Moreover, many of the book's 35 contributors have had immediate and extensive experience in the medical management of terrorist attacks. The book provides insightful and practical information for physicians, nurses, emergency responders, and other health professionals who may be called to service during or after a terror incident. Essentials of Terror Medicine is indispensable reading for the medical community of the 21st century, in which diligence, continued education, and careful preparation for a variety of possible events are a preeminent responsibility.